1996
DOI: 10.1007/bf02458913
|View full text |Cite
|
Sign up to set email alerts
|

Point defects in FeAl

Abstract: Point defects in annealed B2-phase FeAl samples in the range 47-53 at.% Fe were studied using 57Fe MSssbauer spectroscopy. Spectra were analyzed using local environment models according to which point defects in atomic shells close to probe atoms induce shifts in the nuclear monopole interaction. For well-annealed samples, better results were obtained assuming only the presence of Fe~ antisite and VFe vacancy defects, and not of AIFe antisite defects. Monopole interactions of 57Fe probes on the Fe and Al subla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…According to theoretical study [11], the predominant defects in the stoichiometric FeAl B2 structure are vacancies on the Fe sites and the Fe antisites on Al sites, which were confirmed experimentally by Mö ssbauer spectroscopy [12]. The FeAl B2 phase contains a negligible amount of defects such as aluminum antisites and the vacancies on Al sublattices [13].…”
Section: Introductionmentioning
confidence: 89%
“…According to theoretical study [11], the predominant defects in the stoichiometric FeAl B2 structure are vacancies on the Fe sites and the Fe antisites on Al sites, which were confirmed experimentally by Mö ssbauer spectroscopy [12]. The FeAl B2 phase contains a negligible amount of defects such as aluminum antisites and the vacancies on Al sublattices [13].…”
Section: Introductionmentioning
confidence: 89%
“…The development of new, more ductile, Fe-Al alloys depends on a thorough understanding of their properties, implicating a better comprehension of the properties and behaviour of defects in these materials. Experimental [3][4][5] as well as theoretical studies [6][7][8][9][10][11] suggest that iron aluminides present complex point defects, especially double defects. In addition, it has been demonstrated that 'quenched-in' vacancies are responsible for a large strengthening effect both on B2 FeAl [12] and on disordered (A2) Fe-Al alloys [13,14].…”
Section: Introductionmentioning
confidence: 98%
“…It means that thermal defects in B2 FeAl consist of Fe sublattice vacancies and antisite atoms, while constitutional defects consist of Fe antisites in the Fe-rich side and Fe vacancies in the Al-rich side. The triple-defect structure of B2 FeAl has been confirmed also by MS [3] and PAC analysis [2]. It is worth noticing here that no traces of Al-antisites (or vacancies) were detected.…”
Section: Introductionmentioning
confidence: 69%
“…So, it could be suggested that such pre-existing disorder may have affected the final defect structure of B2 FeAl. On the other hand, the atomic arrangement of B2 FeAl may also be influenced by the multiphase composition of analyzed powders as compared to monophase B2 FeAl studied in [1][2][3][4]. However, this assumption needs additional study.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation